Understanding EBLIP at an Organizational Level: An Initial Maturity Model - Thorpe, Clare; Howlett, Alisa (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2020)
Objective - Existing research around evidence based practice in the LIS (library and information science) professional context over the past two decades has captured the experience of individual practitioners, rather than the organization as a whole. Current models of evidence based library and information practice (EBLIP) relate to, and apply predominantly to, individuals or specific scenarios. Yet despite a growing demand from institutional and library leaders for evidence to demonstrate why investments in libraries should continue, little is known about how an organization can enhance its maturity in evidence based practice. This paper addresses this gap by seeking to understand what an evidence based university library looks like and answering the questions: how does a university library leader know the library’s service and practice is evidence based? How can a university library measure and progress its maturity in evidence based practice?Methods - Sixteen semi-structured interviews were conducted with library professionals employed at Australian and New Zealand university libraries. Transcripts were analyzed using thematic analysis techniques. The interviews, combined with a literature review and environmental scan of evidence based practices in university libraries, informed the development of a draft capability maturity model as a framework for developing evidence based practice in university libraries.Results - The model identifies and describes characteristics at five different levels of evidence based practice maturity from least mature (Ad hoc/Sporadic) to most mature (Transforming). Three dimensions of experience help to define the characteristics at each level of maturity and provide a framework to understand how a university library might develop its organizational capacity in evidence based library and information practice.Conclusion - Library leaders and practitioners will benefit from the model as they seek to identify and build upon their evidence based practice maturity, enabling more robust decision-making, a deeper understanding of their clients and demonstration of value and impact to their stakeholders.